Social Changes In Islamic Law Implementation In Indonesia - Syofiati Lubis (Proceeding International Seminar of Islamic Studies, 2019)
Islam came and become a crucial guide to human life which has implications for the changing mankind civilization and the world order. In the regional scope, communities also experience changes over time and space. This paper discusses how changes in Arab society occurred in the range of history to modern society in the Indonesian context. The changes observed in Arab and Indonesian societies are based on social aspects but are closely related to legal changes. In the Indonesian context, across the time the implementations of Islamic law also change because of the complexity of the problems that occur among them in terms of the implementations of Waqf, marriage law and inheritance law in Indonesia. Changes and problems that occur are considered as challenges that need to be responded for the renewal of the compilation of Indonesian Islamic Law (KHI).